'I Do it My Way': The Meaning of Independence in Bandung Indie Musicians and Their Media Uses - Kelana Ashil Siddhawira; Dadang Sugiana (Ikatan Sarjana Komunikasi Indonesia, 2023)
Bandung from various discourses is often referred to as the epicenter of the development of popular culture in Indonesia, including the independent music scene. Along the way, being independent or mostly known as